Prosocial Attitudes of Juvenile Delinquencies - Szíjártó, Lívia (Magyar Rendészet, 2016)
The study analyses the prosocial behaviour in juvenile offenders’ life, their family background and the social interactions. The article reviews the various theories of crime, the concept of prosocial behaviour and the important studies on the social life of offenders. The research comprises of also quantitative and qualitative features. In addition to a questionnaire about prosocial patterns, a semi-structured interview was performed during the study. The interview was done with 107 Hungarian young men between the ages of 14–21. Fifty-five of them are currently serving time in government detention facilities, 52 persons belong to the control group. The results show that the prisoners recognize positive social attitudes, but they are less able to implement them in their behaviour.